The qur’anic sustainable remedy to the global food crisis: Nigeria as a case study (2012)
Agriculturalists, economists and experts from different fields of studies have raised alarm on food crisis. All of the theories propounded did not proffer a sustainable remedy to the invisible catastrophe. Therefore, views of the experts of various fields in both advanced and developing countries were examined. It was discovered that a feasible alternative to sustainable remedy to the global crisis not yet explored is that proffered by the Qur’an. The discussion commenced with the Qur’anic narration on the first food crisis ever witnessed on earth. Reasons and factors responsible for the present global food crisis were examined and compared with the Qur’anic submission on the factor that causes the food crisis. As regards the history of food crisis around the world and in Nigeria, steps taken by the Nigerian government as advised by different experts and agencies were also analyzed. The concept of the Qur’an on the effect of food crisis on the citizenry ended this part. Suggestions put forward by experts and the Qur’an on the global food crisis such as the World Bank, public opinion in doubling financial support to the sector, provision of modern storage facilities, preparation of seeds and distribution of fertilizers to appropriate quarters and period. The recommendations on a sustainable remedy as inferred from the Qur’an and agricultural experts which can boost productivity and enhance availability within a short period ended the discussion.